A modified modulation scheme for three-level diode-clamped matrix converter under unbalanced input conditions - Su, Mei; Zhao, Ziyi; Dan, Hanbing; Peng, Tao; Sun, Yao; Che, Ruyu; Zhang, Fan; Zhu, Qi; Wheeler, Patrick (IET, 2018)
The three-level diode-clamped matrix converter topology has outstanding performance under ideal operating conditions. However, input disturbance can influence the waveforms at the output side of the converter due to the direct coupling between the input and output. This paper proposes a modified modulation scheme for three-level diode-clamped matrix converter during operation with unbalanced input voltages and when different transformer turns ratios are used for an isolation transformer at the input. With this modulation technique, sinusoidal and balanced output voltages are guaranteed and the input current harmonics are minimized. Experimental results are presented to demonstrate the feasibility and effectiveness of the proposed modulation scheme.